Transversal equivalent circuit model of a filter with a surface acoustic wave - URBAŃCZYK, M. (Archives of Acoustics, 1998)
The paper suggests a way of analysis of the operation of the SAW oscillator basing on a computer simulation programme of the electronic systems of the SPICE type. In compliance with the requirements of this programme, an equivalent diagram of a surface wave filter has been presented in a form convenient for computer analysis.